2000
DOI: 10.4049/jimmunol.165.9.5352
|View full text |Cite
|
Sign up to set email alerts
|

Evidence For Early Aging in the Mucosal Immune System

Abstract: Despite recent advances in the cellular and molecular analysis of induction and regulation of mucosal immune responses, little is yet known about differences which occur in aging. To address this important issue, we have compared the mucosal and systemic immune responses of aged (12- to 14-mo- or 2-year-old) and young adult (6- to 8-wk-old) C57BL/6 mice. Both aged and young mice were immunized weekly with three oral doses of 1 mg of OVA and 10 μg of cholera toxin (CT) as mucosal adjuvant. Both groups of mice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 45 publications
5
100
1
2
Order By: Relevance
“…In mice, some reports suggest that, with ageing, the levels of total and specific serum IgG and IgM increase (Koga et al, 2000), while other authors found a reduction in specific IgG and IgM in aged animals (Faria et al, 1998). Speziali et al (2009), have recently shown that basal levels of total serum immunoglobulins, IgG and IgA were increased while antigen-specific immunoglobulins, IgG and IgA were reduced in aged mice compared to young ones.…”
Section: B Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, some reports suggest that, with ageing, the levels of total and specific serum IgG and IgM increase (Koga et al, 2000), while other authors found a reduction in specific IgG and IgM in aged animals (Faria et al, 1998). Speziali et al (2009), have recently shown that basal levels of total serum immunoglobulins, IgG and IgA were increased while antigen-specific immunoglobulins, IgG and IgA were reduced in aged mice compared to young ones.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Speziali et al (2009), have recently shown that basal levels of total serum immunoglobulins, IgG and IgA were increased while antigen-specific immunoglobulins, IgG and IgA were reduced in aged mice compared to young ones. This divergence between total and specific levels of Immunoglobulins, IgG and IgA may reflect the biased repertoire of B cells in aged mice (Koga et al, 2000) and their inability to mount specific immune responses to new antigens. Moreover it has been shown that ageing is followed by an increased production of auto-antibodies in parallel with a diminished production of antibodies against foreign antigens (Weksler and Szabo, 2000).…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Co-administration of adjuvants can increase immunogenicity of mucosally administered antigens (Fujihashi et al, 2000, Kanellos et al, 2000, Choi et al, 2002. Two such mucosal adjuvants, heat labile enterotoxin (LT) from enterotoxinogenic strains of Escherchia coli and its homologue cholera toxin (CT) from…”
Section: Introductionmentioning
confidence: 99%
“…Besides potential use as mucosal adjuvants, the two B-subunits can also serve as vaccines against diarrhea caused by LT and CT as the B-subunit induces high levels of anti-LT-B and anti-CT-B secretory IgA that provide protection against subsequent toxin challenge (Haan et al, 1996, Verweij et al, 1998, Guidry et al, 1997. In addition, our previous studies indicate that oral administration of LT-B corn can induce significant concentrations of anti-LT-B IgG in serum (Fujihashi et al, 2000). For example, vaccines against influenza and tuberculosis are less efficient in aged individuals when compared to young adults (Mayer, 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation